2020
DOI: 10.1016/j.isci.2020.101308
|View full text |Cite
|
Sign up to set email alerts
|

PhotoGal4: A Versatile Light-Dependent Switch for Spatiotemporal Control of Gene Expression in Drosophila Explants

Abstract: Summary We present here PhotoGal4, a phytochrome B-based optogenetic switch for fine-tuned spatiotemporal control of gene expression in Drosophila explants. This switch integrates the light-dependent interaction between phytochrome B and PIF6 from plants with regulatory elements from the yeast Gal4/UAS system. We found that PhotoGal4 efficiently activates and deactivates gene expression upon red- or far-red-light irradiation, respectively. In addition, this optogenetic tool re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Accordingly, there have been several attempts to develop optogenetic binary systems (de Mena et al, 2018). Some success has been reported with optogenetic Gal4 approaches in cell culture, zebrafish embryos, Drosophila, and mice (Liu et al, 2012;Wang et al, 2012;Pathak et al, 2017;de Mena and Rincon-Limas, 2020;Mruk et al, 2020;Yamada et al, 2020). These advances are significant, but they come with some limitations: (i) the long light exposure (in the order of hours) necessary to induce phenotypes or reporter expression (de Mena and Rincon-Limas, 2020; Mruk et al, 2020), likely incompatible with live imaging or the study of rapid biological processes; (ii) leakiness in the dark (Mruk et al, 2020;Pathak et al, 2017;Yamada et al, 2020); (iii) the lack of a fully transgenic optogenetic Gal4/UAS system (Liu et al, 2012;Pathak et al, 2017;Yamada et al, 2020); or (iv) the requirement of an exogenous chromophore, which is only readily administered to tissue explants (de Mena and Rincon-Limas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there have been several attempts to develop optogenetic binary systems (de Mena et al, 2018). Some success has been reported with optogenetic Gal4 approaches in cell culture, zebrafish embryos, Drosophila, and mice (Liu et al, 2012;Wang et al, 2012;Pathak et al, 2017;de Mena and Rincon-Limas, 2020;Mruk et al, 2020;Yamada et al, 2020). These advances are significant, but they come with some limitations: (i) the long light exposure (in the order of hours) necessary to induce phenotypes or reporter expression (de Mena and Rincon-Limas, 2020; Mruk et al, 2020), likely incompatible with live imaging or the study of rapid biological processes; (ii) leakiness in the dark (Mruk et al, 2020;Pathak et al, 2017;Yamada et al, 2020); (iii) the lack of a fully transgenic optogenetic Gal4/UAS system (Liu et al, 2012;Pathak et al, 2017;Yamada et al, 2020); or (iv) the requirement of an exogenous chromophore, which is only readily administered to tissue explants (de Mena and Rincon-Limas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other light-gated expression systems have been developed in Drosophila, including the cryptochrome split-LexA and Photo-Gal4 [59,60]. We expressed the cryptochrome split-LexA with the same driver used to test LOV-LexA, LC10s-SS2 [20], and found that cryptochrome split-LexA system is leaky in flies raised at 18ºC and kept in the dark (data not shown).…”
Section: Discussionmentioning
confidence: 91%
“…The spatial resolution provided by Photo-GAL4 remains unmatched by LOV-LexA in vivo, due to the scattering that occurs once light traverses the cuticle in pupal and adult flies. Given that Photo-GAL4 relies on PhyB and requires addition of the chromophore PCB, normally absent in animal cells, it is currently limited to ex vivo studies [59]. The chromophore providing LOV with light sensitivity is flavin mononucleotide that exists in animal cells, making the LOV-LexA system solely dependent on delivery of light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations